Digital Industry: Talent Mapping and Triple Helix Partnerships for Strengthening Services Exports - Yoki Muchsam; Mochamad Afrizal Maulana; Cegunawan Cegunawan; Mulfi Sandi Yuda (Eastasouth Institute, 2026)
The digital industry is rapidly expanding and serves as a crucial driver of the global economy. However, developing countries like Indonesia are confronted with a significant digital talent gap and insufficient structured collaboration among government, industry, and academia, which hinders their competitiveness in the digital services export market. This study aims to review academic and policy literature on digital talent mapping and the Triple Helix model (government, industry, academia) as strategic tools to enhance digital services exports, particularly in emerging economies like Indonesia. Employing a systematic literature review (SLR) methodology, the study follows five phases: problem identification, literature search, inclusion and exclusion criteria, data extraction and synthesis, and thematic analysis, synthesizing insights from 25 publications dated between 2023 and 2025. The findings reveal that advanced economies have effectively integrated talent mapping with the Triple Helix model to foster growth in digital services exports. In contrast, Indonesia faces several challenges, including outdated curricula, a lack of integrated labor market data, and weak cross-sectoral coordination. The study highlights the necessity for further research to explore innovative solutions and collaborative frameworks that can address these challenges, ultimately enhancing Indonesia's capacity to compete in the global digital services market.